Schools That Change : Evidence-Based Improvement and Effective Change Leadership. - Smith, Lewis (Lew) (SAGE Publications, 2007)
Through specific examples, qualitative research, and portraiture, the author illustrates how and why some schools are able to achieve significant, sustainable change while others cannot.